Analysis of Knowledge Management and Total Quality Management Implementation: A Study on Indonesian Small and Medium Enterprises - Roy Qurrotu Ainin; Dinda Fitria Ningrum (Journal of Investment Development, Economics and Accounting, 2024)
This study deals specifically with analyzing the implementation of Knowledge Management (KM) and Total Quality Management (TQM) in Small and Medium Enterprises (SMEs) in Indonesia. The purpose is to analyze the implementation of KM Elements and TQM Practices in SMEs in Indonesia and identify the challenges faced by SMEs in Indonesia in implementing TQM and KM. This article is based on information about SMEs in Indonesia that are recorded in the digital ecosystem of 27 million in December 2023. . The primary and secondary data collected were analyzed using content analysis techniques with a qualitative approach. The results show that the most applied Knowledge Management Elements (KME) are "Knowledge Application" and "Knowledge Acquisition" and the most applied Integrated Quality Management (TQMP) practices by SMEs in Indonesia are "Continuous Improvement". Keywords Total Quality Management, Knowledge Management, TQM practices, KM elements, Indonesian  Small and Medium Enterprises